2019
DOI: 10.1093/ibd/izz185
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Quality of Life in Inflammatory Bowel Disease: A Multicenter, National-Level Study

Abstract: Background The impact of inflammatory bowel disease (IBD) on sexual health is a leading concern among patients. Most studies focus on sexual dysfunction rather than patient-perceived sexual quality of life (SQoL). We aimed to assess SQoL in IBD patients compared with healthy controls. Methods This is a multicenter, cross-sectional study of IBD patients (n = 575 with Crohn’s disease and n = 294 with ulcerative colitis), compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Furthermore, the same study reported depression and previous surgery as significant predictors of ED in men and depression and anemia as significant SD predictors in men 9 . Roseira et al performed a multicentre cross‐sectional study of IBD patients in Portugal and have found age, widow status and depression to be independent predictors of sexual QOL in men and depression as only independent predictor in women 23 . Results from our study were partly in line showing also depression as significant ED and SD predictor in men, and additionally in multivariate analysis we have revealed several male ED predictors (emotional and systemic IBDQ domain) and male SD predictors (emotional IBDQ domain, disease duration and UC phenotype).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the same study reported depression and previous surgery as significant predictors of ED in men and depression and anemia as significant SD predictors in men 9 . Roseira et al performed a multicentre cross‐sectional study of IBD patients in Portugal and have found age, widow status and depression to be independent predictors of sexual QOL in men and depression as only independent predictor in women 23 . Results from our study were partly in line showing also depression as significant ED and SD predictor in men, and additionally in multivariate analysis we have revealed several male ED predictors (emotional and systemic IBDQ domain) and male SD predictors (emotional IBDQ domain, disease duration and UC phenotype).…”
Section: Discussionmentioning
confidence: 93%
“…However, only a few modifiable factors affecting FPP decision-making in patients with IBD can be identified; these are mostly related to the mode of the patients' access to FPP-related information. Some IBD-related issues (impaired body image, sexuality, partnership) might be modifiable through psychological interventions [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The main predictor of reduced quality of life associated with sexual health was depression, demonstrating that the main concerns of IBD patients in this area of life are related to emotional and self-esteem issues closely associated with body image. 16 Individuals with IBD report significant concerns, which should be considered in the holistic model of care because they influence the disease selfmanagement and thus health outcomes. The main concerns were related to loss of bowel control, the risk of developing cancer, the association between stress and illness, the chronicity of the disease, and fatigue.…”
Section: Discussionmentioning
confidence: 99%